"Who steals my purse steals trash...": reputation as a factor in establishing the value of non-executive directors and members of audit committees. (1st January 2000) - Page, Michael; Spira, Laura F.
Independent audit is a key corporate governance mechanism and the involvement of non-executive directors in audit committees has been promoted as a method of improving the accountability of company management to investors. Grout et al. [1] suggested that qualified independence of auditors is a signalling device; auditors will be vulnerable to loss if their acquiescence in marginally acceptable accounting practices is not backed by well-founded belief in the stability of their client. This paper extends this model to non-executive directors (NEDs) and members of audit and remuneration committees of large UK corporations, suggesting that the threat of the loss of reputation plays a similar role in the efficacy of NEDs as a signalling device. This hypothesis is tested by using titles and honours bestowed by the UK Government as a proxy for reputation. NEDs are found to be six times as likely to hold honours as executive directors.